Servant Leadership and Innovative Work Behavior: The Mediation Role of Flow at Work and Trust - Rifa Rahmah Edyawati, Dhea; Mega Desiana, Putri (IPB University, 2024)
Competitiveness in the context of digital business encourages companies to continuesly innovate in their daily operations to achieve market dominance and adapt to changes in environmental forces and competitor strategies. Innovative Work Behavior (IWB) of employees is considered to be an important element for companies to carry out sustainable innovation. This research aims to determine the influence of Servant Leadership (SEL) on IWB as well as the mediating role of Flow at Work (FAW) and Trust (TR) between the relationship between SEL and IWB. This research used the survey of 247 employees from digital business companies using Structural Equation Modeling (SEM) as a data analysis method. The research results show that the majority of employees working in digital business companies feel that their desire to engage in innovative behavior is influenced by the role of their supervisor who demonstrate servant leadership characteristics as well as a feeling of flow that makes employees feel total involvement in completing their work. SEL plays a significant role in increasing employee IWB and FAW is proven to partially mediated the relationship between SEL and IWB. Meanwhile, in the indirect effect of TR, it was identified that TR did not mediate the relationship between SEL and IWB. This research is expected to provide insights for company HR management in increasing the active role of employees' innovative behavior in the workplace.